How to join and stay in the Olympic COVID-free "bubble"? - Su, Z.; McDonnell, D.; Cheshmehzangi, A.; Ahmad, J.; Šegalo, S.; da Veiga, C. P.; Xiang, Y. T. (Brain, Behavior, & Immunity - Health, 2022)
The Beijing, 2022 Olympics will be the second Games held amid the COVID-19 pandemic. Due to the unique circumstances the 2022 Games face—the Omicron spread, high virus transmissibility in winters, and uncertainties about vaccine efficacy and future variants of concern, safety measures amid the Beijing, 2022 Games will be one of the most intricate among large international events held during the pandemic. To ensure athletes' health, safety, and ability to participate in the Games, the organizers have introduced the Olympic COVID-free "bubble" protection ecosystem, in which COVID-free athletes could stay and be protected from potential infections that could upend their Games plans, if not their career as well. However, while staying in the "bubble" is key for athletes' health and success, there is a lack of insights on factors that might prevent athletes from continuing their scheduled Olympic journey as scheduled. To shed light on the issue, based on Beijing, 2022 Olympic Playbooks and most up-to-date guidance issued, this article and its accompanying infographic were developed to illustrate factors that could influence athletes` ability to join and stay in the "bubble", participate in the Games, and further build their career. Furthermore, we also adapted and integrated easy-to-adopt mental health de-stress techniques recommended by the World Health Organization to help athletes better thrive amid the Beijing, 2022 Winter Olympics, in or outside of the "bubble".